2023
DOI: 10.1097/brs.0000000000004586
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes Following Anterior and Posterior Surgical Approaches for Multilevel Cervical Myelopathy

Abstract: Study Design. Retrospective cohort. Objective. To compare health-related quality of life (HRQoL) outcomes between approach techniques for the treatment of multilevel degenerative cervical myelopathy (DCM). Summary of Background Data. Both anterior and posterior approaches for the surgical treatment of cervical myelopathy are successful techniques in the treatment of myelopathy. However, the optimal treatment has yet to be determined, especially for multilevel disease, as the different approaches have separate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The incidence rate of axial symptoms (AS) can be as high as 29.9% after ACDF [ 22 ] and 46.7% after ACCF [ 23 ], respectively. The pathophysiology of neck pain is complicated, and most likely associated with disc degeneration, herniation, and the loss of cervical lordosis, as well as bio-mechanical abnormality of facet joints, muscles, and ligaments [ 24 , 25 ]. The loss of cervical lordosis and even cervical kyphosis may gradually develop due to the long-term bad lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of axial symptoms (AS) can be as high as 29.9% after ACDF [ 22 ] and 46.7% after ACCF [ 23 ], respectively. The pathophysiology of neck pain is complicated, and most likely associated with disc degeneration, herniation, and the loss of cervical lordosis, as well as bio-mechanical abnormality of facet joints, muscles, and ligaments [ 24 , 25 ]. The loss of cervical lordosis and even cervical kyphosis may gradually develop due to the long-term bad lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…We implemented a minimum clinically important difference (MCID) of 15 of 100, which Carreon et al established using an anchor-based technique. 3,22 To ensure our study would be adequately powered, we performed an a priori sample size calculation, which showed that at least 50 patients in each group would reliably detect a difference in means of 15 points with 80% power and an alpha of 0.05. 23…”
Section: Methodsmentioning
confidence: 99%
“…We implemented a minimum clinically important difference (MCID) of 15 of 100, which Carreon et al established using an anchorbased technique. 3,22 To ensure our study would be adequately powered, we performed an a priori sample size calculation, which showed that at least 50 patients in each group would reliably detect a difference in means of 15 points with 80% power and an alpha of 0.05. 23 Secondary outcomes included changes in neurological function according to the modified Japanese Orthopedic Association (mJOA) scale, neck and arm pain according to Numerical Rating Scales (scored from 0 to 10 points), and quality of life according to Short Form 12 Physical and Mental Component Summaries and EuroQol 5D, from baseline to 1 year after surgery.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations